Complimentary Imaging Modalities for Investigating Obscure Gastrointestinal Bleeding: Capsule Endoscopy, Double-Balloon Enteroscopy, and Computed Tomographic Enterography - Ye Chu; Sheng Wu; Yuting Qian; Qi Wang; Juanjuan Li; Yanping Tang; Tingting Bai; Lifu Wang (Gastroenterology Research and Practice)
Objectives. The complimentary value of computed tomographic enterography (CTE) and double-balloon enteroscopy (DBE) combined with capsule endoscopy (CE) was evaluated in the diagnosis of obscure gastrointestinal bleeding (OGIB). Methods. Patients who received CE examinations at Ruijin Hospital between July 2007 and July 2014 with the indication of OGIB were identified, and those who also underwent DBE and/or CTE were included. Their clinical information was retrieved, and results from each test were compared with findings from the other two examinations. Results. The overall diagnostic yield of CE was comparable with DBE (73.9% versus 60.9%) but was significantly higher than the yield of CTE (87% versus 25%, p<0.001). The diagnostic yield of angiodysplasia at CE was significantly higher than CTE (73% versus 8%, p<0.001) and DBE (39.1% versus 17.4%, p=0.013), while no significant difference was found between the three approaches for small bowel tumors. DBE and CTE identified small bowel diseases undetected or undetermined by CE. Conversely, CE improved diagnosis in the cases with negative CTE and DBE, and findings at initial CE directed further diagnosis made by DBE. Conclusions. Combination of the three diagnostic platforms provides complementary value in the diagnosis of OGIB.